2006
DOI: 10.1124/dmd.106.012153
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Metabolism in Mice of IDN 5390 (13-(N-Boc-3-i-butylisoserinoyl)-C-7,8-seco-10-deacetylbaccatin III), a New Oral C-seco-Taxane Derivative with Antiangiogenic Property Effective on Paclitaxel-Resistant Tumors

Abstract: ABSTRACT:IDN 5390 (13-(N-Boc-3-i-butylisoserinoyl)-C-7,8-seco-10-deacetylbaccatin III) is a new taxane, derived from 7,8-C-seco-10-deacetylbaccatin, selected for its ability to inhibit angiogenesis, mainly by acting on endothelial cell motility, and for its selective activity on class III ␤-tubulin. In vivo, IDN 5390 shows activity against paclitaxel-sensitive and -resistant tumors when administered on a prolonged, continuous dosage schedule. We studied the pharmacokinetics and bioavailabilty of the drug in mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…The structure of M2 (RT, 10.9 min) could not be ascertained from the fragment ions. In parallel with hydroxylation sites of paclitaxel and some other taxanes (Cresteil et al, 2002;Frapolli et al, 2006), we propose C6␣ as the possible hydroxylation site for M2 (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The structure of M2 (RT, 10.9 min) could not be ascertained from the fragment ions. In parallel with hydroxylation sites of paclitaxel and some other taxanes (Cresteil et al, 2002;Frapolli et al, 2006), we propose C6␣ as the possible hydroxylation site for M2 (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the primary monooxygenases changed from CYP2C8 to CYP3A4 (Cresteil et al, 2002;Taniguchi et al, 2005). Interestingly, when both phenyls at C3Ј of C13 side chain were replaced by the alkyl or alkenyl group, the major hydroxylation site was again moved from tert-butyl back to the isobutyl or isobutenyl group, such as SB-T-1102, SB-T-1214, SB-T-1216 (Gut et al, 2006), and IDN5390 (Frapolli et al, 2006). All of these results suggested that substituents at C3Ј determined taxane metabolism with regard to the site of hydroxylation and the P450 isoform implicated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1B) to the CYP3A4-catalyzed hydroxylation at tert-butyl of the side chain (Cresteil et al, 2002;Taniguchi et al, 2005). It is interesting to note that when both phenyl and benzamide at C3Ј of C13 side chain were replaced by N-␣-tert-butyloxycarbonyl amino group and an alkyl or alkenyl group, respectively, the major hydroxylation site was again moved from tert-butyl to the alkyl group (Frapolli et al, 2006;Gut et al, 2006). Zhang et al (2008) investigated how different substitutes at the C3Ј position of taxane analogs affected its metabolism with cephalomannine and paclitaxel, a pair of analogs that differ slightly at the C3Ј position.…”
Section: Discussionmentioning
confidence: 99%
“…The compound is a C-4 methyl carbonate analog of paclitaxel that contains additional modifications in the side chain where the two phenyl groups of paclitaxel were replaced by t-butyl groups (Bröker et al, 2007). BMS-275183 exhibited good oral bioavailability in both rat and dog and showed antitumor activity comparable with intravenous paclitaxel (Frapolli et al, 2006).[ 14 C]BMS-275183 was metabolized to oxidative metabolites in liver microsomes of animals and humans and in bile duct-cannulated rats Kim-Kang et al, 2002). Only trace amounts of conjugated metabolites were detected in rat bile.…”
mentioning
confidence: 99%